2021
DOI: 10.3390/healthcare9020179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Balance Shoes on Balance and Postural Stability in the Elderly: A Crossover, Controlled, Randomized Single-Blind Study

Abstract: The risk of falling increases with age. Individuals wearing unadapted shoes present an aggravating risk factor. The objective of this study was to determine the effectiveness of specifically designed balance shoes on balance and postural stability in healthy elderly people compared to that of their usual shoes. In total, 21 healthy individuals aged 65–84 years (76.0 ± 8.0 years) performed balance tests (bipedal with open or closed eyes, unipedal with open eyes, limits of stability, and step cadence) while wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…The ndings of this study need to be interpreted in the context of several limitations. First, although previous research has shown that ve weeks of habituation to new shoes does not signi cantly affect standing balance or gait patterns in older women [43], previous studies have used a habituation period of between 25 metres [19], one minute [20] and a few days [44]. In our study, participants were only provided with a brief period of time to acclimatise to the different footwear conditions before undertaking the balance tests.…”
Section: Discussionmentioning
confidence: 99%
“…The ndings of this study need to be interpreted in the context of several limitations. First, although previous research has shown that ve weeks of habituation to new shoes does not signi cantly affect standing balance or gait patterns in older women [43], previous studies have used a habituation period of between 25 metres [19], one minute [20] and a few days [44]. In our study, participants were only provided with a brief period of time to acclimatise to the different footwear conditions before undertaking the balance tests.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study need to be interpreted in the context of several limitations and highlight that these data represent only a preliminary evaluation of the footwear given the relatively small sample. First, although previous research has shown that 5 weeks of habituation to new shoes does not significantly affect standing balance or gait patterns in older women [ 44 ], previous studies have used a habituation period of between 1 min [ 19 , 20 ] and a few days [ 45 ]. In our study, participants were only provided with a brief period of time to acclimatise to the different footwear conditions before undertaking the balance tests.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors found no significant differences in anteriorposterior oscillations. In contrast, shoes produce instability, decrease rate of force development and indirect ground reaction force (GRF) transmission, thereby compromising lifting performance (3,15,20). Contrary, the barefoot lifting could be considered more efficient than shod lifting by integration of the force × velocity curve during the concentric phase and resulting in better motor control that contribute with a steady state sooner which could potentially explain the increased rate of force development while barefoot (3,21).…”
Section: Discussionmentioning
confidence: 99%
“…All participants performed a routine of resistance training programs used an intensity between 60% and 80% 1RM and a routine of strength training that engaged the whole body with resistance bands, free-weights, dumbbells and medicine balls. The personal shoes selected were shoes usually worn during daily activities within the last 2 months (15). The participants were eligible if they weren't smokers for the previous 3 months or more, had no cardiovascular or metabolic diseases, systemic hypertension (140/90 mm Hg or use of antihypertensive medication), recent musculoskeletal injury and surgery (in the last 6 months), or pain in any region of the body, and had not used anabolic steroids, drugs or any medication with the potential to impact physical performance (self-reported).…”
Section: Participantsmentioning
confidence: 99%